From risk to prevention: diabetes screening in an urban community of Uttara Kannada district - Singh, Shubhangini; Sanjay, P. H. V.; Tawar, Shabeena; Singh, Harpreet (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes is rapidly increasing in India due to urbanization, sedentary habits and unhealthy lifestyles. Early identification of high-risk individuals is essential to prevent complications. The Indian Diabetes Risk Score (IDRS) is a simple, low-cost tool that can be used in community settings. To assess the risk of type 2 diabetes among adults aged 30–70 years in an urban community using the IDRS and to identify associated socio-demographic and lifestyle factors. Methods: A cross-sectional study was carried out among 448 adults selected through systematic random sampling in an urban field practice area of Uttara Kannada district, Karnataka. Data were collected using a structured questionnaire and anthropometric measurements. Diabetes risk was categorized as low, moderate or high using the IDRS tool. Associations were tested using chi-square analysis. Results: Older age, sedentary lifestyle, positive family history and increased waist circumference were significantly associated with higher diabetes risk. Central obesity was the strongest predictor. Conclusions: More than half of the study population was at moderate-to-high risk of diabetes. Incorporating IDRS-based screening into primary health care and community programs can help in early detection and prevention.